HARACTERISTICS OF INJURIES RECEIVED DURING AN EARTHQUAKE AND ORGANIZATION OF PROVIDING FIRST AID TO THE POPULATION IN EMERGENCY SITUATIONS BY RESCUERS - Khachatryan, Ashkhen (Crisis Management and Technologies, 2025)
Earthquakes are one of the most terrible natural disasters, claiming tens and hundreds of of thousands of human lives and causing devastating destruction over vast areas. The article presents the nature of injuries received by the population in the earthquake focus and the elimination of medical consequences, in particular, the organization of the provision of timely medical care to the population by the rescue service of the Ministry of Internal Affairs of the Republic of Armenia, civil defense units. In general, it can be concluded that the development of programs for the prevention of emergency situations, the reduction and elimination of their possible consequences, the provision of timely first aid to the population in case of various injuries, will contribute to more effective implementation of the above complex measures, as a resulting in a decrease in the number of adverse outcomes.